2022
DOI: 10.1002/app.52786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of electrical trees degradation of crosslinked polyethylene at high temperatures by electron‐buffering voltage stabilizers

Abstract: The effect of adding electron-buffering voltage stabilizer (1 wt% maminobenzoic acid) on the electrical tree-induced degradation of cross-linked polyethylene (XLPE) was studied at high temperatures. The electrical tree inception, growth, and partial discharge characteristics were simultaneously analyzed at 30, 50, and 70 C, respectively. The results showed that the growth rate of electrical tree and partial discharge activity as well as the discharge repetition rate, significantly increased with the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Adding voltage stabilizers to the insulation prevents the electric field from being distorted at high voltages, 33,34 and changing the crosslinking method by using different crosslinkers also stabilizes the electric field. To investigate the electrical properties of the insulation layer after crosslinking initiated by various crosslinkers, we calculated the distribution of potential in the insulation layer using COMSOL Multiphysics (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding voltage stabilizers to the insulation prevents the electric field from being distorted at high voltages, 33,34 and changing the crosslinking method by using different crosslinkers also stabilizes the electric field. To investigate the electrical properties of the insulation layer after crosslinking initiated by various crosslinkers, we calculated the distribution of potential in the insulation layer using COMSOL Multiphysics (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Adding voltage stabilizers to the insulation prevents the electric field from being distorted at high voltages, 33,34 and changing the crosslinking method by using different crosslinkers also stabilizes the electric field.…”
Section: Insulation Performance Of Pe Doped With Different Crosslinkersmentioning
confidence: 99%
“…One approach to the development of new high breakdown strength material is compounding voltage stabilizer molecules into polyethylene, which can then be further crosslinked. [2][3][4][5][6][7][8][9] Chen and co-workers 7 have also tried to use nanofillers in cross-linked polyethylene and found that the addition of nanofillers typically will decrease the electrical insulation performance. The study of voltage stabilizers has a history of more than half a century.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐linked polyethylene is an important and widely utilized material for power transmission cables. One approach to the development of new high breakdown strength material is compounding voltage stabilizer molecules into polyethylene, which can then be further cross‐linked 2–9 . Chen and co‐workers 7 have also tried to use nanofillers in cross‐linked polyethylene and found that the addition of nanofillers typically will decrease the electrical insulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the urgent requirement for offshore wind power transmission and urbanization has led to the development of power cables (mainly cross-linked polyethylene [XLPE] cables). [1][2][3][4] With the continuous increase in voltage levels, frequent failures occur in cable accessories, due to their complex structures and challenges in multilayered insulation coordination. This significantly constrains the stable operation of power systems.…”
Section: Introductionmentioning
confidence: 99%